Effectiveness of glycerol-monooleate in high-performance polymer tribo-systems. (March 2021) - Jiang, Shaoli; Yuan, Chengqing; Wong, Janet S.S.
Abstract: High performance polymers possessing superior mechanical properties may replace metal components and improve machine efficiency. Successful replacement, however, relies on the compatibility of these polymers with current engineering systems, including lubricants and their additives. This study examines the compatibility of two high performance polymers, polyetheretherketone (PEEK) and polyamide-imide (PAI), with glycerol monooleate (GMO), an organic friction modifier (OFM) commonly used in steel-steel rubbing contacts. Friction tests were conducted with a ball-on-disc geometry in reciprocating motion at 100 °C in polyalphaolefin (PAO) base oil. GMO reduces friction in polymer-steel and polymer-polymer contacts. When steel is involved, the use of GMO and oleic acid (OA) give similar friction coefficients. Since OA is believed to be a hydrolyzed product of GMO in steel-steel contacts, our results show that the interaction of OA with steel controls friction in polymer-steel contacts when GMO is the additive. Results from FTIR and Raman spectroscopies show that steel surfaces contain little to no polymeric materials, nor iron oxides after rubbing against polymers in GMO- and OA-containing PAO. This supports OFM layers are formed on steel surfaces. These OFM layers prevent polymer transfer layer formation and possibly protect steel surfaces from oxidation. Our results show that using OFM that interacts strongly with steel can, contrary to dry friction, eliminate the need of polymeric transfer film on steel for achieving low friction in polymer-steel contacts. Highlights: GMO reduces friction of PEEK- and PAI- steel contacts. GMO and oleic acid give similar friction reduction in PAI-steel contacts. GMO is more effective than oleic acid in PAI-PAI contacts. GMO may not have hydrolysed to oleic acid in PAI-PAI contacts. Polymer transfer to steel surface is prevented by the use of friction modifiers.